2010
DOI: 10.1097/ijg.0b013e31819c4679
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Factors Influencing Glaucoma Treatment Adherence

Abstract: Purpose To understand the factors that influence glaucoma treatment adherence with medication taking, prescription refills, and appointment keeping in order to develop an intervention for a specific population. Patients and Methods In-depth interviews were conducted with 80 individuals diagnosed with open angle glaucoma, glaucoma suspect, or ocular hypertension. Additional eligibility requirements were that all participants were: between the ages of 18–80; White or African American; spoke and understood Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
3
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 32 publications
2
79
3
11
Order By: Relevance
“…In addition, frequent doctors' visits promote the doctor-patient relationship, which may also account for a better medication adherence. 19 In contrast, other factors such as age or education level, which were found as determinants for medication adherence in chronic eye diseases such as glaucoma, had no significant influence on the use of AREDS supplements in our study. Similarly, Friedman et al 20 did not consistently find age as a significant risk factor for poor adherence.…”
Section: Discussioncontrasting
confidence: 64%
“…In addition, frequent doctors' visits promote the doctor-patient relationship, which may also account for a better medication adherence. 19 In contrast, other factors such as age or education level, which were found as determinants for medication adherence in chronic eye diseases such as glaucoma, had no significant influence on the use of AREDS supplements in our study. Similarly, Friedman et al 20 did not consistently find age as a significant risk factor for poor adherence.…”
Section: Discussioncontrasting
confidence: 64%
“…For some patients this includes multiple medications instilled several times per day. Previous studies have shown that patients commonly miss eye drop doses [1][2][3][4][5][6] and that poor adherence is associated with more severe visual field loss. 7 Kass et al, 1 using an electronic dose monitor, found that 62% of patients omitted 10% of doses and 15% of patients omitted 50% of doses.…”
Section: Introductionmentioning
confidence: 99%
“…26 Qualitative research methods have been used in the study of glaucoma, specifically to gain insight regarding quality of life, 27,28 barriers to receiving eye care, 8,9,29 patient education, 30,31 and adherence to care recommendations. 6,11,18 Although some of these studies have noted family and social support factors as important considerations, they have not specifically focused on asking individuals in the social support network of patients with glaucoma for their perspectives and how they relate to the perspectives of the individuals with glaucoma.…”
Section: Discussionmentioning
confidence: 97%
“…2 Prior work by other investigators have identified many possible factors contributing to this problem, including lack of patient understanding of glaucoma and its treatment, lack of patient adherence to treatment recommendations, inability to afford either medications or medical care, other barriers to access to care, and innate aggressiveness of disease in some patients. [3][4][5][6][7][8][9][10][11] Despite this research, we continue to struggle with effectively treating patients-even those with access to eye care providers. Identification of the reasons that patients continue to lose vision from glaucoma despite being within the health care system is critical.…”
mentioning
confidence: 96%